2021
DOI: 10.1097/md.0000000000026582
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of potential key genes in active tuberculosis

Abstract: Background: Tuberculosis (TB) is a global health problem that brings us numerous difficulties. Diverse genetic factors play a significant role in the progress of TB disease. However, still no key genes for TB susceptibility have been reported. This study aimed to identify the key genes of TB through comprehensive bioinformatics analysis.Methods: The series microarray datasets from the gene expression omnibus (GEO) database were analyzed. We used the online tool GEO2R to filtrate differentially expressed genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
1
9
1
2
Order By: Relevance
“…In the brown module, we also identified STAT1 hub-central TF, a pivotal component of the JAK鈥揝TAT signaling pathway and a signal transducer and transcription activator that mediates cellular responses to IFNs, cytokines, and growth factors ( Hall et al, 2020 ). Interestingly, M. bovis counteracts the immune response by suppressing STAT1 expression and exacerbates its pathogenesis in the host cells ( Chen J. et al, 2021 ). Studies in patients with active TB have shown that STAT1 activation was impaired in host macrophages ( Esquivel-Sol铆s et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brown module, we also identified STAT1 hub-central TF, a pivotal component of the JAK鈥揝TAT signaling pathway and a signal transducer and transcription activator that mediates cellular responses to IFNs, cytokines, and growth factors ( Hall et al, 2020 ). Interestingly, M. bovis counteracts the immune response by suppressing STAT1 expression and exacerbates its pathogenesis in the host cells ( Chen J. et al, 2021 ). Studies in patients with active TB have shown that STAT1 activation was impaired in host macrophages ( Esquivel-Sol铆s et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine tuberculosis (bTB) is domestic livestock's infectious and chronic respiratory disease, especially in beef and dairy cattle (Brosch et al, 2002;Waters et al, 2012;Hall et al, 2021), which has paramount economic, animal welfare, and public health consequences. Despite implementing management strategies to control and eradicate it, bTB is still a major global health threat to animal populations (Vegh et al, 2015;Lu et al, 2021). Econometric analysis has ranked bTB as the fourth most important cattle disease, causing ~$3 billion in annual losses to global agriculture (Garnier et al, 2003;McLoughlin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Within macrophages, intracellular Mtb can promote NF-魏B pathway activation, in turn leading to GBP induction and the inhibition of caspase-3 activation, thus preventing macrophages from undergoing apoptotic death such that Mtb can thrive and replicate within these host cells [30]. Multiple reports have shown Mtb infection to be linked to the upregulation of a range of GBPs including GBP1-7, with elevated levels of these genes being linked to the risk of disease progression [31,32]. ATF3 (activating transcription factor 3) is an ATF/cAMP response element-binding transcription factor that can reportedly modulate the upregulation of proinflammatory cytokines through binding to the NF-魏B p65 subunit [33].…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados experimentales obtenidos por los investigadores indicaron que los tubos de calor super largos con una relaci贸n L/D extremadamente grande, pueden trabajar con un correcto funcionamiento. Chen et al [10] realiz贸 un estudio experimental sobre un tubo de calor extralargo asistido por gravedad de gran relaci贸n L/D (>5000),donde se observan los reg铆menes de flujo multif谩sico al interior del tubo de calor y como estos se relacionaban como el rendimiento del dispositivo. En base a los resultados de la experimentaci贸n, se observ贸 que el termosif贸n super largo funciona en cuatro reg铆menes de flujo distintos, uno de ellos provocado directamente por la alta relaci贸n L/D utilizada.…”
Section: Introductionunclassified
“…El r茅gimen de ebullici贸n en g茅iser donde la temperatura de la superficie muestra fluctuaci贸n peri贸dica. La ebullici贸n en g茅iser es m谩s probable que ocurra en tubos de calor super largos con alta relaci贸n L/D [10]. La ebullici贸n en g茅iser es un fen贸meno de inestabilidad que pueden presentar los termosifones, est谩 relacionada con la expansi贸n abrupta del vapor en el evaporador [11].…”
Section: Introductionunclassified